Race and Virulence Determination of Fusarium oxysporum f. sp. cubense Isolates from Sidomulyo Village of Bantul, Yogyakarta - Herika Novrelly Jayatri; Christanti Sumardiyono; Arif Wibowo (Jurnal Perlindungan Tanaman Indonesia, 2018)
Banana is one of the important fruit crop in Village of Sidomulyo, Bantul, Yogyakarta. One of important diseases which become the constraint in development of banana is Fusarium wilt caused by Fusarium oxysporum f. sp. cubense (Foc). This fungus has high race diversity and  virulence, so that it required early detection for prevention and control of disease. This experiment was aimed to figure out race and virulence of Foc isolates from Village of Sidomulyo, Bantul, Yogyakarta. The 13 tested isolates were isolates of PR11, PKJ20, RU20, PR30, AH40, PKJ40, A41, RB42, PR43, RU51, A60, RP60, and A80. Race was molecularly detected using two types of primers, i.e. General Foc primer FocEf3 and specific primer for race 4 (Foc-1/Foc-2). Virulence test was performed on banana seedlings of Ambon Kuning cultivar using Completely Randomized Design (CRD) with 14 treatments and 4 repetitons. The observed parameters were external and internal symptoms, calculation of disease severity index and disease intensity. Data were analyzed using variance and further test of Duncan Multiple Range Test (DMRT) at 5 % level. The results showed that all isolates were Foc and 9 of 13 isolates were grouped into race 4, i.e. A80, RP60, PR11, A41, AH40, PKJ40, PR30, RB42, and PR43. The highest and lowest virulences were consecutively expressed by PR30, RB42, RU51, RP60, PR43, PKJ40, PR11, A41, AH40, RU20, PKJ20, A60, and A80, with severity index on leaves and rhizomes ranging 1.61-2.91 and 2.25-7, respectively. IntisariPisang merupakan tanaman buah unggulan di Desa Sidomulyo Kecamatan Bambanglipuro, Kabupaten Bantul. Salah satu penyakit penting yang menjadi kendala dalam pengembangan pisang adalah layu fusarium yang disebabkan oleh jamur Fusarium oxysporum f. sp. cubense (Foc). Jamur ini memiliki keragaman ras dan virulensi yang tinggi, sehingga deteksi dini diperlukan untuk pencegahan dan pengendalian penyakit. Penelitian ini bertujuan untuk mengetahui ras dan virulensi isolat Foc asal Desa Sidomulyo, Kecamatan Bambanglipuro, Kabupaten Bantul. Isolat yang diuji sebanyak 13 isolat, yakni isolat PR11, PKJ20, RU20, PR30, AH40, PKJ40, A41, RB42, PR43, RU51, A60, RP60, dan A80. Pengujian ras secara molekuler dengan menggunakan dua jenis primer yakni primer Foc in general FocEf3 dan primer spesifik ras 4 Foc-1/Foc-2. Uji virulensi pada bibit kultivar ambon kuning dengan menggunakan Racangan Acak Lengkap (RAL) yang terdiri dari 14 perlakuan dan 4 ulangan. Parameter yang diamati berupa pengamatan gejala luar dan gejala dalam, penghitungan indeks keparahan penyakit dan intensitas penyakit. Analisis data menggunakan sidik ragam dan uji lanjut Duncan Multiple Range Test (DMRT) pada taraf 5 %. Hasil pengujian menunjukkan bahwa semua isolat merupakan isolat Foc dan dari 13 isolat yang digunakan terdapat 9 isolat yang merupakan ras 4 yakni isolat A80, RP60, PR11, A41, AH40, PKJ40, PR30, RB42, dan PR43. Isolat yang memiliki virulensi tertinggi sampai terendah berturut-turut adalah PR30, RB42, RU51, RP60, PR43, PKJ40, PR11, A41, AH40, RU20, PKJ20, A60, dan A80, dengan indeks keparahan pada daun berkisar 1,61−2,91 dan indeks keparahan pada bonggol 2,25−7.